2D MXenes as Perspective Immobilization Platforms for Design of Electrochemical Nanobiosensors. Issue 10 (29th May 2019) - Lorencova, Lenka; Gajdosova, Veronika; Hroncekova, Stefania; Bertok, Tomas; Blahutova, Jana; Vikartovska, Alica; Parrakova, Lucia; Gemeiner, Pavol; Kasak, Peter; Tkac, Jan
Abstract: MXenes are a new group of 2D nanomaterials with fascinating properties including high electrical conductivity, hydrophilic nature, easily tunable structure and high surface area. This is why MXene modified interfaces are extremely promising for the preparation of sensitive electrochemical biosensors. While there are numerous reports on MXene‐based enzymatic biosensors for detection of a wide range of analytes, application of MXene for construction of affinity biosensors is in its infancy. The review article summarizes current state‐of the‐art in the field with a focus on MXene modifications needed for construction of robust and high performance MXene electrochemical biosensors. Abstract :